Optimization of Tooling Design for Hot Mandrel Bending of Pipe Elbows - Diekmann, Uwe; Homberg, Werner; Prehm, Jens; Rostek, Tim; Schönhoff, Nils; Tabakajew, Dmitri; Trasca, Andreea; Uysal, Haris (Materials Science Forum)
This paper presents the finite element model developed for the simulation of pipe elbow production by the so-called ‘Hamburg process’ in order to improve productivity and resource efficiency. To optimize the tooling design, a sensitivity analysis of the tool parameters that influence the quality of pipe elbows, such as mandrel height and length, is conducted. Different materials data sets including damage models were considered. Using numerical simulations, it is possible to determine an optimized tool geometry for the production of specific pipe elbow dimensions. Furthermore, as a result of the experiments and numerical simulations conducted, it is possible to increase the production velocity of the serial plant. Along with deformation, damage models are included in simulations in order to identify the right process boundaries. Finally, an experimentally validated model is developed for increasing resource efficiency in pipe elbow fabrication.

Grading Technologies for the Tanufacture of Innovative Cutting Blades - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 1960, 100013)

Hybride Verbundstrukturen aus Aluminium und Titan für Leichtbauanwendungen - Homberg, Werner; Rostek, Tim; Schaper, Mirko; Grydin, Olexandr; Andreiev, Anatolii; Brosius, Alexander; Guilleaume, Christina

Herstellung innovativer Stahlhalbzeuge mit wanddicke- und festigkeitsveränderlichen Eigenschaften für den Leichtbau durch Innendrückwalzen (IDW) - Wiens, Eugen; Homberg, Werner

Internal Flow-Turning – extended manufacturing possibilities in tailored tube production - Wiens, Eugen; Homberg, Werner (MATEC Web of Conferences)

LHYBS – Lightweight Design by Novel Hybrid Materials - Camberg, Alan Adam; Tröster, Thomas; Heggemann, Thomas; Homberg, H.; Schaper, Mirko; Dietrich, J.; Bremser, Wolfgang; Achterberg, L.; Kabst, M.; Wille, M.; Peckhaus, Volker

Friction-spinning—Grain structure modification and the impact on stress/strain behaviour - Lossen, Benjamin; Andreiev, Anatolii; Stolbchenko, Mykhailo; Homberg, Werner; Schaper, Mirko (Journal of Materials Processing Technology)

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Intrinsically lubricated tool inserts for deep drawing applications generated by selective laser melting - Bader, Fabian; Hengsbach, Florian; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)
Abstract. Within the scope of this study, an intrinsically lubricated deep drawing die fabricated via laser beam melting (LBM) is investigated. In contrast to the common objective of generating highly dense LBM components, this work endeavors to achieve intended micro-scale porosity. By utilizing permeable structures, in-process closed-loop control of lubrication during the forming operations is feasible. Based on a modified AM scan strategy, the required filigree, porous structures can be generated. Thus, in the present work three permeable specimens are additively generated from the maraging steel 1.2709. The cylindrical specimens are then analyzed via light microscopy (LM), microcomputer tomography (microCT), and with regard to the oil throughput rate. Subsequently, an intrinsically lubricated, AM deep drawing tool die is manufactured and experimentally tested. The findings reveal interesting results for deep drawn specimens with AM deep drawing dies.

Al2O3/ZrO2-8Y2O3 and (Cr,Ti)AlSiN tool coatings to influence the temperature and surface quality in friction-spinning processes - Tillmann, Wolfgang; Fehr, Alexander; Stangier, Dominic; Dildrop, Markus; Homberg, Werner; Lossen, Benjamin; Hijazi, Dina (Production Engineering)
Friction-spinning is an incremental forming process, which is accompanied by complex thermal and mechanical loads in the tool and the formed part. To influence the process temperature, two main process parameters, i.e. the rotation speed and the feed rate, can be adapted. With the objective to improve the tool performance and the quality of the workpiece, this study focuses on a coating concept for friction-spinning tools made of high speed steel (HS6 5 2C, 1.3343). On the one hand, atmospheric plasma sprayed (APS) Al2O3 and ZrO2-8Y2O3 coatings serve as a thermal insulator, and, on the other hand, physically vapor deposited (PVD) TiAlSi7.9N and CrAlSi7.5N films are applied to increase the hardness and wear resistance of the tools. In addition, duplex coatings, combining the APS and PVD technique, are synthesized to influence both the heat transfer and the tribological properties of friction-spinning tools. Subsequently, all coated tools are tested in a friction-spinning process to form flanges made of AW-6060 (AlMgSi 3.3206) tube materials. The tool temperatures are determined in-situ to investigate the impact of the tool coating on the process temperature. Compared to an uncoated tool, the alumina and zirconia coatings contribute to a reduction of the tool temperature by up to half, while the PVD films increase the hardness of the tool by 20 GPa. Furthermore, it is shown that the surface quality of thermally sprayed (TS) or PVD coated tools is directly related to the surface roughness of the resulting workpiece.